Browning Intensity and Taste Change Analysis of Chicken Protein–Sugar Maillard Reaction System with Antioxidants and Different Drying Processes. Issue 2 (21st September 2016) - Zeng, Xiaofang; Bai, Weidong; Zhu, Xinwu; Dong, Hao
Abstract: Inhibitory effects of several antioxidants on the browning intensity of chicken protein–sugar Maillard reaction system were investigated. The results found that 1% (m/v) addition of NaCl had a certain effect on inhibiting browning, while only 0.5% (m/v) addition of L‐cysteine can play a favorable role in browning inhibition. As for MRP samples with L‐ascorbic acid, the browning inhibiting effect reaches the max with the L‐ascorbic acid content of 0.3% (m/v). The A420 value of samples dried by spray drying process was higher ( P  < 0.05) than those of chicken protein Maillard peptide and enzymatic hydrolysate dealt by freeze drying process. The electronic tongue analysis indicated that the umami substances of chicken protein Maillard peptide could be easily decompose in the process of storage, while those of enzymatic hydrolysate were stable. However, compared with the spray drying process, freeze drying process can better preserve umami substances. Practical Applications: The inhibitory effect of several antioxidants, including NaCl, L‐cysteine, polyphenols and L‐ascorbic acid, on the browning intensity of chicken protein–sugar Maillard reaction system was identified. In the meantime, the effects of two kinds of drying technologies (spray drying technology and freeze drying technology) on the properties and browning intensity of Maillard peptides were also compared and discussed. Results obtained in this work can provide practical application in food industry.